Early Coronary Angiography and Survival After Out-Of-Hospital Cardiac Arrest - Vyas, Ankur (Circ Cardiovasc Interv, 2015)
BACKGROUND: While out-of-hospital cardiac arrest is commonly due to acute myocardial infarction, it is unknown whether early coronary angiography is associated with improved survival in these patients. METHODS AND RESULTS: Using data from the Cardiac Arrest Registry to Enhance Survival (CARES), we identified 4,029 adult patients admitted to 374 hospitals after successful resuscitation from out-of-hospital cardiac arrest due to ventricular fibrillation, pulseless ventricular tachycardia or unknown shockable rhythm between January 2010 and December 2013. Early coronary angiography (occurring within one calendar day of cardiac arrest) was performed in 1953 (48.5%) patients, of whom 1253 (64.2%) received coronary revascularization. Patients who underwent early coronary angiography were younger (59.9 vs. 62.0 years); more likely to be men (78.1% vs. 64.3%), have a witnessed arrest (84.6% vs. 77.4%), and have ST-elevation myocardial infarction (32.7% vs. 7.9%); and less likely to have known cardiovascular disease (22.8% vs. 35.0%), diabetes (11.0% vs. 17.0%), and renal disease (1.8% vs. 5.8%; P<0.01 for all comparisons). In analysis of 1312 propensity score-matched pairs, early coronary angiography was associated with higher odds of survival to discharge (OR: 1.52, [95% CI 1.28–1.80]), P<0.0001) and survival with favorable neurological outcome (OR 1.47, [95% CI 1.25–1.71], P<0.0001). Further adjustment for coronary revascularization in our models significantly attenuated both ORs, suggesting that revascularization was a key mediator of the survival benefit. CONCLUSIONS: Among initial survivors of out-of-hospital cardiac arrest due to VF or pulseless VT, we found early coronary angiography was associated with higher odds of survival to discharge and favorable neurological outcome.